The effect of party identification and party cues on populist attitudes - Diogo Ferrari (Research & Politics, 2022)
In recent years, a wave of populist leaders has emerged in many democratic countries, including the United States. Previous studies have argued that populist rhetoric matters for leaders’ electoral support because the public has populist attitudes, which are activated in contexts of failure of democratic governance or economic crises. This paper investigates the opposite causal direction and argues that people’s support for populist ideas can be an effect rather than a cause of leaders’ electoral support. People who support a candidate due to the candidate’s party affiliation or policy position tend to support or oppose populist or anti-populist messages if they learn that the candidate of the party they identify with supports that message. The paper investigates the argument with an experiment that randomly assigns (anti-)populist messages and a cue about the candidate that supports the message. The experiment shows that voters’ party identification largely affects support for both populist and anti-populist messages.